2019
DOI: 10.1016/j.cognition.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic spillovers: Learning others’ political views reduces the ability to assess and use their expertise in nonpolitical domains

Abstract: Highlights Participants believe politically like-minded others are better at unrelated tasks. They turn to the politically like-minded even when others are more accurate. Participants are more influenced by politically like-minded others on those issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 27 publications
5
38
0
4
Order By: Relevance
“…For example, Marks et al . [13], found that the similarity with one’s political views affects one’s ability to make accurate assessment about their fellow’s expertise in the domain of geometric shapes. Moreover, trusting in-group politicians (especially when they are powerful leaders) can happen even when this implies spreading disinformation [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Marks et al . [13], found that the similarity with one’s political views affects one’s ability to make accurate assessment about their fellow’s expertise in the domain of geometric shapes. Moreover, trusting in-group politicians (especially when they are powerful leaders) can happen even when this implies spreading disinformation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although participants were unaware of this correlation, hobbies may have been inadvertently perceived as reliable cues by the participants, or simply perceived as more appealing information to view. It is also possible that this unexpected finding represents a form of "normative prestige", where participants wanted to copy players who had similar hobbies or viewpoints to them 28 . However, the copying rates in the first pilot study were unexpectedly low, and so this result should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Marks, Copland, Loh, Sunstein, and Sharto (2019) Nonetheless, on the basis of research in moral psychology, we expected that shared moral values with an expert would continue to drive deference among a subset of people. This is because some people believe that moral values can be objectively right or wrong (Goodwin & Darley, 2008 (Kant, 2012(Kant, /1785Nagel, 1986).…”
Section: Moral Truth and Tribalismmentioning
confidence: 99%